The Influence of Principal’s Instructional Leadership, Infrastructure, and Teacher Professional Development on the Quality of Learning in Senior High School - Retnawati, Lina; Egar, Ngasbun; Br Ginting, Rosalina (SAINTIS Publishing, 2025)
This study aims to analyze the influence of principal instructional leadership, infrastructure, and teacher professional development on learning quality in public senior high schools (SMA Negeri) in Blora Regency. A quantitative approach with an associative research design was employed to examine the relationship between these variables. The research involved 200 teachers as respondents, selected through proportional random sampling. Data were collected using a structured questionnaire and analyzed using descriptive and inferential statistical methods, with the assistance of SPSS Statistics Version 26. The findings reveal that all three independent variables significantly influence learning quality. Principal instructional leadership has a strong positive effect on learning quality, with a correlation coefficient of 0.918 and an impact of 84.2%. Infrastructure also plays a crucial role, showing a correlation coefficient of 0.872 and contributing 76% to learning quality. Teacher professional development demonstrates a strong correlation of 0.890, influencing 79.2% of learning quality. The multiple regression analysis indicates that these three factors simultaneously explain 86.6% of the variance in learning quality, while the remaining 13.4% is influenced by other factors outside the model. The study concludes that effective principal instructional leadership, adequate infrastructure, and continuous teacher professional development are key determinants in enhancing learning quality. Schools with strong leadership, well-maintained facilities, and active teacher training programs tend to achieve higher educational outcomes. These findings emphasize the importance of a holistic approach in improving learning quality through leadership empowerment, facility enhancement, and professional teacher development. Future research is recommended to explore additional factors affecting learning quality, such as curriculum implementation, student motivation, and parental involvement. Policymakers and school administrators should prioritize leadership training, facility investment, and professional development programs to optimize the quality of education in Blora Regency and beyond.